The Effect of Combination of Nitrogen and Phosphate Enrichment on the Development of Seaweed Spores (Kappaphycus alvarezii) - Sahir, Muhammad; Rustam, Rustam; Latama, Gunarto; Herliyanti, Herliyanti; Damayanti, Nur Ulfa (Torani Journal of Fisheries and Marine Science, 2022)
Seaweed (Kappaphycus alvarezii) is one of the aquatic commodities that has the potential to be developed due to demand reaching the international market (Ari, SP and Risna Yusuf, 2018). Provision of seeds is still carried out by vegetative means (cuttings) (Runtuboy N and Slamet Abadi, 2018). However, there are problems, especially the provision of quality seeds, large scale, and does not depend on the season. Provision of seeds can also be done generatively. K. alvarezii can be developed by exploiting the nature of sexual reproduction through the development of spores which are characterized by the presence of cystocarp on the surface of the thallus (Juniarta I, 2016). However, the cystocarp in its growth really needs nutrition in order to produce spores of good quality and quantity. The nutrients needed are nitrogen and phosphate. This is due to the role of nitrogen as a constituent of protein and phosphate as a provider of energy (Pauwah A, et al., 2020). The purpose of this study was to determine the dose ratio of nitrogen and phosphate enrichment on cystocarp development. The research was carried out from November 2018 to February 2019, at the Seaweed Laboratory of the Takalar Brackish Water Aquaculture Fishery Center (BPBAPT). The study contained 6 treatments with 3 repetitions, namely Treatment A = Without enrichment (SW), Treatment B = 0.5 ppm N: 0.5 ppm P, Treatment C = 1 ppm N: 0.5 ppm P, Treatment D = 1.5 ppm N : 0.5 ppm P, Treatment E = 0.5 ppm N : 1 ppm P, and Treatment F = 0.5 ppm N : 1.5 ppm P. The results showed that the highest germination was in treatment D with an average of 56.95%. However, the research was not significantly different between treatments (p>0.05).